Analisis Strategi Pemasaran dalam Meningkatkan Omzet Penjualan Peternakan Itik Petelur Zhianfa Farm di Nagari Tigo Koto Silungkang, Kecamatan Palembayan, Kabupaten Agam - Dessi Mayunis; Yuwarman Mansur (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This research is motivated by the problems faced by the Zhianfa Farm egg-laying duck farming business, including a decreasing increase in net income in 2023, a lack of labor in distributing products, and promotional activities that have not been carried out optimally. This study aims to determine the marketing strategies implemented in an effort to increase sales turnover in the Zhianfa Farm egg-laying duck farming business. The type of research used is a field study with a qualitative approach. Informants in this study consisted of the business owner and two customers of the egg-laying duck farming business. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were then analyzed using a SWOT analysis followed by the preparation of an IFE matrix, an EFE matrix, a SWOT matrix, and an analysis of the score weight table. Data sources in this study include primary data and secondary data. Based on the results of the research on the Zhianfa Farm egg-laying duck farming business, it can be concluded that the most appropriate marketing strategy to increase sales is the SO strategy with a score of 3.59. The SO strategy is a strategy that utilizes all internal strengths to seize opportunities owned by the Zhianfa Farm egg-laying duck farming business. The SO strategies that can be implemented include: (1) maintaining and improving the quality of superior duck eggs to meet the still large market, (2) utilizing good farm management and strategic locations, (3) maintaining relatively affordable prices to maintain consumer loyalty, and (4) developing value-added duck products by utilizing superior egg quality.